PENGARUH IKLIM KERJA DAN KOMITMEN PEGAWAI TERHADAP KINERJA MELALUI KEPUASAN KERJA PEGAWAI DI SMK NEGERI 1 SUMBERASIH - PROBOLINGGO - jurnalpps pps; Siti Khodijah AB (Prodi Magister Manajemen Universitas Wijaya Putra, 2020)
This study aims to determine and explain the effect of work climate variables on employee performance, the effect of employee commitment to employee performance; the influence of the work climate on employee job satisfaction; influence of employee commitment to employee job satisfaction, influence of work climate, employee commitment and job satisfaction on performance. This type of research used in this research is explanatory research with a quantitative approach. Data collection techniques using instruments in the form of questionnaires, research data were analyzed using simple and multiple correlation techniques, as well as using regression equations, multiple linear, F test and t test. The variables in this study are the work climate and employee commitment including independent variables, job satisfaction as a mediator variable and employee performance as the dependent variable. This study uses data obtained from questionnaires by respondents. The data analysis method used is Analysis Path. The results showed that the work climate and employee commitment significantly influence job satisfaction; work climate, employee commitment and job satisfaction significantly and positively influence the performance of the employees of SMK Negeri 1 Sumberasih.Keywords: work climate, employee commitment, job satisfaction, employee performance.